INOVASI BISNIS JASA FASHION DENGAN PENDEKATAN DESIGN THINKING DAN BUSINESS MODEL CANVAS OLEH WIRAUSAHAWAN RINTISAN PEKERJA MIGRAN INDONESIA DI TAIWAN PADA MASA PANDEMI COVID-19 - M Ghufran Ramdhani; Beni Dwi Komara (PROCEEDING UMSURABAYA, 2022)
Many people create new products or services that fail to be accepted by customers. While innovation is needed to solve a complex problem faced by customers. This study aims to find out how the fashion business innovation process uses the design thinking method and the business model canvas carried out by Indonesian migrant workers in Taiwan during the Covid-19 pandemic. This research uses qualitative descriptive, through interviews, observations and documentation studies of the implementation of helping online entrepreneurship workshops conducted by the University of Muhammadiyah Gresik in collaboration with CLC-BJI Taiwan. From the research results, fashion business innovation starts from the empathy process to understand the problems of the PMI Taiwan Muslim target customers in terms of meeting the needs of Islamic clothing. Next, process the idea by observing existing solutions, Crazy 8 and having discussions to determine a solution called Ummul Syari by making a business prototype using the Go-Sew and Instagram applications which were tested on customers with very positive ratings. The business model that has been designed is validated to the stakeholders involved, concluding that the partners, key resources and customer elements have been validated and the business is feasible to continue. the results of the Desirability, Feaseability and Visibility tests of ummul syar'i businesses are fairly valid, all from the results of interviews with respondents.Keywords: Business Model Canvas; Design Thingking; Pekerja Migran Indonesia; Pandemi Covid-19